A novel Sn-based coordination polymer with high-efficiency and ultrafast lithium storage. (20th January 2022) - Zhang, Xinlu; Han, Lu; Li, Junfeng; Lu, Ting; Li, Jinliang; Zhu, Guang; Pan, Likun
Highlights: A Sn-based coordination polymer with high electrical conductivity was fabricated. The Sn-DHTPA was evaluated as an anode material for LIBs. High capacity, ultrafast Li storage and good cycling performance were achieved. The lithium storage mechanism was studied by a series of ex-situ characterizations. Abstract: Recently, Coordination Polymers (CPs) have been widely utilized as energy storage materials for reversible Lithium-Ion Batteries (LIBs) benefiting from their tunable building blocks and adjusted electrochemical properties. However, the unsatisfied electrochemical behavior of CPs with poor conductivity and sluggish ion transport kinetics is still a bottle-neck for their large-scale energy storage applications in LIBs. Herein, we display the rational fabrication of a conductive Sn-based coordination polymer (Sn-DHTPA) via judiciously choosing suitable building units. The Sn-DHTPA is employed as anode for LIBs, exhibiting superior reversible storage capacity of 1142.6 mA h g −1 at 0.1 A g −1 after 100 cycles and impressive rate storage capability of 287.7 mA h g −1 at 20 A g −1 . More importantly, a robust cycling performance of 205.5 mA h g −1 at an extra-high current density of 20 A g −1 are observed without remarkable capacity-fading up to 1000 cycles. The behavior superiority of Sn-DHTPA is related to its advanced architecture with abundant lithium storage sites, high electrical conductivity and rapid lithium transport. A series of ex-situ characterizations reveal that the impressive lithium storage capacity is contributed by the redox active sites of both the aromatic linker and metal center related to in-situ generated metallic nanoparticles dispersed in the skeleton. Graphical abstract: Image, graphical abstract